Atmospheric blocking signatures in total ozone and ozone miniholes - Barriopedro Cepero, David; Antón Martínez, Manuel; García García, José Agustín (American Meteorological Society, 2010)
© 2010 American Meteorological Society. This work has been partially supported by the MICINN (Spanish government) under Projects CGL2007-65891-C05-05/CLI (DB and JAG) and CGL2008-05939-C03-02/CLI (M. Anton). ERA-40 reanalysis data were provided by the ECMWF from their data server Web site (http://www.ecmwf.int/). MA thanks Junta de Extremadura-Consejeria de Infraestructuras y Desarrollo Tecnologico-and Fondo Social Europeo for concession of a postdoctoral grant. R. R. Garcia provided helpful comments on this manuscript. Two anonymous reviewers contributed to improving the final version of this paper. This paper analyzes the statistical relationship between the total ozone column (TOC) and atmospheric blocking using 40-yr European Centre for Medium-Range Weather Forecasts (ECMWF) Re-Analysis (ERA-40) data for the 1978-98 period, with special emphasis on winter and the European and eastern Pacific sectors. Regional blocking occurrence is accompanied by a decrease of TOC within the anticyclonic circulation region and a distinctive ozone increase upstream and downstream (upstream and south) in the Pacific (European) sector. Blocking significantly enhances the likelihood of low TOC extremes, especially over the Scandinavian and the Alaska Peninsulas, where more than 50% of winter blocks lead to TOC values in the lowest tail of the distribution. The relationship between ozone miniholes and blocking is confined to the high latitudes of both basins and is strong in Europe, where about half of the ozone miniholes occur simultaneously with blocking. Blocking-related ozone miniholes (blocking ozone miniholes) are also among the most intense and persistent. Although blocking activity does not drive the interannual variability of regional ozone miniholes, blocking ozone miniholes account for up to two-thirds of the total observed trend of ozone miniholes in Europe. The polar vortex is proposed as a feasible candidate for explaining the enhanced coupling of blocking and ozone miniholes in Europe and its long-term ...